Viscoelastic-Viscoplastic Modelling of the Scratch Response of PMMA - G. Kermouche; N. Aleksy; J. M. Bergheau (Advances in Materials Science and Engineering)
This paper aims at understanding how to model the time-dependent behavior of PMMA during a scratch loading at a constant speed and at middle strain levels. A brief experimental study is first presented, consisting of the analysis of microscratches carried out at various scratching velocities and normal loads. The loading conditions have been chosen in such a way that neither (visco)elasticity nor (visco)plasticity of the PMMA may be neglected a priori. The main analyzed parameter is the tip penetration depth measured during the steady state. Then, a finite element model is used to investigate the potential of classical elastic-viscoplastic constitutive models to reproduce these experimental results. It is mainly shown that these models lead to unsatisfying results. More specifically, it is pointed out here that the time-independent Young modulus used in such models is not suitable. To take into account this feature, a viscoelastic-viscoplastic model based on the connection in series of a viscoelastic part with a viscoplastic part is proposed. It is shown that it leads to more acceptable results, which points out the importance of viscoelasticity in the scratch behavior of solid polymers.